Antihypertensive control and new-onset atrial fibrillation: Results from the Swedish Primary Care Cardiovascular Database (SPCCD). (29th August 2020) - Mourtzinis, Georgios; Schiöler, Linus; Kahan, Thomas; Bengtsson Boström, Kristina; Hjerpe, Per; Hasselström, Jan; Manhem, Karin
Abstract: Background: Atrial fibrillation is associated with increased cardiovascular morbidity and mortality. Hypertension is an important risk factor for the development of atrial fibrillation. Aim: This study assessed the relationship between blood pressure control and new-onset atrial fibrillation in hypertensive patients. Methods and results: We followed 45, 530 hypertensive patients with no previously documented atrial fibrillation, attending primary healthcare in Sweden during 2001–2008. After a mean follow-up of 3.5 years 2057 patients (4.5%) developed atrial fibrillation. Compared to patients with no atrial fibrillation, the new-onset atrial fibrillation group (after adjustment for age, sex, diabetes mellitus, heart failure, ischaemic heart disease, cerebrovascular disease and number of visits) had higher mean in-treatment systolic blood pressure (SBP) and diastolic blood pressure of 3.8 mmHg (95% confidence interval (CI) 3.0–4.6; P  < 0.0001) and 1.6 mmHg (95% CI 1.2–2.0; P  < 0.0001), respectively. Similarly, mean in-treatment pulse pressure in the new-onset atrial fibrillation group was 2.2 mmHg (95% CI 1.6–2.9; P  < 0.001) higher. In a logistic regression analysis, achieved SBP ≥ 140 mmHg was associated with a higher risk of new-onset atrial fibrillation, compared to SBP 130–139 mmHg (odds ratio (OR) 1.5; 95% CI 1.3–1.7) and to SBP < 130 mmHg (OR 1.3; 95% CI 1.1–1.5). There was no difference in risk for new-onset AF between SBP 130–139 and <130 mmHg (OR 0.9; 95% CI 0.7–1.1). Conclusion: The present findings indicate that blood pressure control in hypertension is associated with a lower risk of new-onset atrial fibrillation.